PERTUMBUHAN DAN HASIL TIGA VARIETAS SORGUM (Sorghum bicolor (L.) Moench) DI TANAH RAWA AKIBAT APLIKASI AMELIORAN TULANG SAPI - Parwito, Parwito; Susilo, Edi; Illahi, Noteka; Togatorop, Eny Rolenti; Pujiwati, Hesti (Department of Agronomy, Faculty of Agriculture, University of Mataram and Indonesian Society of Agronomy, NTB Branch, 2023)
Sorghum has the potential to be developed considering that this plant is easy to cultivate in various types of soil and various climatic conditions. The purpose of this study was to determine the dose of bovine bone ameliorant on the growth and yield of sorghum in swampland and to determine the interaction of ameliorant and varieties of sorghum cultivated in swampland. This research is expected to provide information about the effect of giving cow bone ameliorant to several varieties of sorghum in swamps. The research was carried out from February to April 2020, in Gunung Alam Village, Arga Makmur District, Bengkulu Utara Regency. The study used a Completely Randomized Block Design with 12 treatments and 6 replications. The treatment used in this study consisted of two factors, namely the first factor was bovine bone ameliorant with 2 levels, namely bovine bone ameliorant treatment and without beef bone ameliorant treatment. The second factor of sorghum varieties, namely Numbu, Super 1, and Super 2. The results showed that the 50 g dose of beef bone ameliorant gave the highest value in this study.